Quantifying the Colonization of Environmental Microbes in the Fish Gut: A Case Study of Wild Fish Populations in the Yangtze River - Yang, Haile; Wu, Jinming; Du, Hao; Zhang, Hui; Li, Junyi; Wei, Qiwei (Frontiers in Microbiology, 2022)
In aquatic animals, gut microbial communities shift with host development and living environments. Understanding the mechanism by which the environment impacts the gut microbial communities of aquatic animals is crucial for assessing and managing aquatic ecosystem health. Here, we proposed a simplified framework for the colonization and dynamics of gut microbial communities. Then, to quantify the colonization of environmental microbes in the wild fish gut, the current study used 16S rRNA gene amplicon sequencing to obtain the structure of the water environmental microbial community and the gut microbial community in 10 fish populations from the Wuhan section of the Yangtze River, and the relationship of these microbial communities was analyzed. The results identified that in most individuals, nearly 80% of gut microbes (at the operational taxonomic unit (OTU) level) were shared with the water environmental microbial community. In most individuals, more than 95% of microbe species (OTUs) in the gut were transient. For fish species, more than 99% of microbe species (OTUs) that were introduced into the gut were transient. Nearly 79% of OTUs and 89% of species of water environmental microbes could be introduced into the fish gut. Driven by the introduction of transient microbes, fishes with similar feeding habits had similar gut microbial communities. The results indicated that for adult fishes, most gut microbiota were transient from the environmental microbiota that were related to fish feeding habits. We therefore encourage future research to focus on environmental microbiota monitoring and management to promote the better conservation of aquatic animals. It was important to note that, because of various impact factors, interspecific differences and individual variations on gut microbial community characteristics, the quantification of gut microbes in the current work was approximate rather than accurate.